THE FIGURES OF SPEECH IN VOGUE’S ADVERTISEMENTS - Helena Aritonang; Sri Juriati Ownie (LINGUISTICA, 2013)
ABSTRACT The objectives of this research were to describe the twelve types of figures of speech namely lexical metaphor, namely: metaphor, simile, personification, synecdoche, metonymy, symbol, allegory, overstatement, apostrophe, understatement, verbal irony and the one that dominant and also explain what does the dominant mean in Vogue’s advertisements. This research was conducted by using the qualitative and quantitative design. It took fifteen advertisements taken randomly from Vogue’s magazine which were published from October 2011 until January 2012. The result showed that there are only five figures of speech were used in the advertisements of Vogue’s magazine, they are : hyperbole, personification, simile, metaphor and allegory.